Niñez migrante en Colombia: grises del aclamado estatuto temporal de protección (Tema Central) - Pelacani, Gracy (2022)
This article critically analyses the child rights-based approach of the Temporary Protection Statute for Venezuelan Migrants adopted by Colombia in March 2021, to question if it responds to the protection needs of Venezuelan children. The Statute recognizes that having a regular migratory status is a prior and necessary step for the full guarantee of children rights. Therefore, at first, the study considers how the Colombian State has responded to some of the main protection challenges of Venezuelan children in Colombia and the gaps that remains in the actions undertaken. Then, it delves into the way in which the Temporary Protection Statute aims at granting access to a regular migratory status and the protection of the rights of Venezuelan children in Colombia. This article concludes that the Temporary Protection Status is a necessary but insufficient advance for the protection of migrant children rights. This is so because it perpetuates a limited and biased view of migration and promotes the creation of a double standard of protection that prejudices children of nationalities other than the Venezuelan.